An Explanation for the Equality between Inertia and Gravitational Mass - SANDU, Constantin; BRASOVEANU, Dan (JOURNAL OF ADVANCES IN PHYSICS, 2017)
The mechanism causing the equality of inertia and gravitational mass of a body, which was demonstrated experimentally by Eotvos in 1909 is still unexplained although this equality is the basis of Einsteins General Theory of Relativity (GTR). Using consequences of GTR, this paper explains why the inertia mass is equally to the gravitational mass. The two masses are equal because the mechanism that produces the inertia ˜force of a body is the same with the ’mechanism’ that produces the gravitational force of the same body.